Differences in Learning Outcomes and Student Activities Taught Using Project Based Learning and Discovery Learning Models on Electrolyte and Non-Electrolyte Solution Materials - Siregar, Tanti Armalia; Muchtar, Zainuddin (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
Differences in Learning Outcomes and Student Activities Taught Using Project Based Learning and Discovery Learning Models on Electrolyte and Non-Electrolyte Solution Materials. This research aims to find out whether there are differences in learning outcomes and learning activities for students who are taught using project based learning and discovery learning. The sample in this research was students of class X IPA 1 as experimental class 1 and X IPA 2 as experimental class 2. This research used quantitative research methods. The data taken in this research are student learning outcomes collected through student posttest scores to measure student learning outcomes and student learning activity observation sheets to measure student activity during the learning process. However, before testing the hypothesis, prerequisite tests are carried out, namely homogeneity and normality tests. The research results showed that there were differences in learning outcomes and student learning activities between experimental class 1 which was taught by implementing PjBL modeling compared to experimental class 2 which was taught by implementing DL modeling. Evidence of this can be given referring to the mean value of learning outcomes for experimental class 1 students which is higher than experimental class 2. Likewise, the learning activities of experimental class 1 students are higher than experimental class 2. From the results of the hypothesis test, using the t test it was found that the significance value smaller than 0.00 < 0.05, so H0 is rejected and Ha is accepted.Keywords : Learning outcomes, student learning activities, Problem Based Learning, Discovery Learning. Doi: 10.23960/jppk.v13i2.30054